Teknologi Membran Dalam Pengolahan Limbah Cair Industri - Hermana Setti Tarigan; Jhon Armedi Pinem; Idral Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Membrane technology began to be developed at this time. The low energy needed in the operation of membrane technology is one of the triggers for this technology to develope. Stages of the process carried out is the process of coaguulation-flocculation to reduce membrane work and ultrafiltration processes with operating pressures of 1, 3, and 5 bars. The results obtained are the highest percentage of rejection UF membrane process obtained at a pressure of 5 bar that is equal to 84.92% BOD5; 84.71% COD; and 62.5% TSS with an average flux value of 53.69 L/m2.hour.Membrane-based processes with pressure thrust such as microfiltration, ultrafiltration, nanofiltration, and reserve osmosis have been widely used in water and wastewater treatment processes. The wastewater used in this study came from one of the pulp and paper industries. Keywords: Pulp and paper wastewater, Ultrafiltration, Coagulation, Flocculation, rejection